2021
DOI: 10.3389/fmicb.2021.655165
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Programming of Drought-Challenged Trichoderma harzianum-Bioprimed Rice (Oryza sativa L.)

Abstract: Trichoderma biopriming enhances rice growth in drought-stressed soils by triggering various plant metabolic pathways related to antioxidative defense, secondary metabolites, and hormonal upregulation. In the present study, transcriptomic analysis of rice cultivar IR64 bioprimed with Trichoderma harzianum under drought stress was carried out in comparison with drought-stressed samples using next-generation sequencing techniques. Out of the 2,506 significant (p < 0.05) differentially expressed genes (DEGs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…The application of Trichoderma to wheat triggers systemic defense pathways [ 40 ] and seems to be a good choice to minimize damage caused by abiotic stresses [ 35 , 37 ], also limiting environmental pollution. There is sufficient evidence to consider that Trichoderma association can help plants in sustaining drought stress by increasing: (i) the expression of antioxidative enzymes that alleviate the damage caused by the accumulation of ROS and modulating the balance of plant’s phytohormones [ 25 , 41 ]; (ii) the absorption surface that leads the plant to improve water-use efficiency [ 33 ]; and (iii) the synthesis of phytohormones and phytohormonal analogues to promote plant performance.…”
Section: Introductionmentioning
confidence: 99%
“…The application of Trichoderma to wheat triggers systemic defense pathways [ 40 ] and seems to be a good choice to minimize damage caused by abiotic stresses [ 35 , 37 ], also limiting environmental pollution. There is sufficient evidence to consider that Trichoderma association can help plants in sustaining drought stress by increasing: (i) the expression of antioxidative enzymes that alleviate the damage caused by the accumulation of ROS and modulating the balance of plant’s phytohormones [ 25 , 41 ]; (ii) the absorption surface that leads the plant to improve water-use efficiency [ 33 ]; and (iii) the synthesis of phytohormones and phytohormonal analogues to promote plant performance.…”
Section: Introductionmentioning
confidence: 99%
“…Water deficit stress significantly inhibits crop productivity and quality. Trichoderma inoculation could ameliorate the negative effect of water deficit stress and facilitate growth promotion in plants ( De Palma et al, 2016 ; Bashyal et al, 2021 ). Mastouri et al (2010 , 2012) demonstrated the effects of Trichoderma inoculation on plant performance to be apparent only in stressful environments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NT33 and NT3 increased the chlorophyll content in the drought susceptible genotypes as compared to non-inoculated controls, which is an important pigment essential for absorbing light during photosynthetic process ( Table 3 ). Bashyal et al (2021) reported that genes related to the photosynthesis process, such as those coding for photosystem I subunits, photosystem II core complex proteins, osmotin like proteins, and stomatal development were upregulated in the Trichoderma inoculated plants as compared to non-inoculated controls. Water deficit exposed plants inoculated with Trichoderma exhibit improved physiological health ( Shukla et al, 2012 ; Harman et al, 2019 ; Khoshmanzar et al, 2020 ), similar to our observation in NT33-colonized tomato plants.…”
Section: Discussionmentioning
confidence: 99%
“…44 Trichoderma harzianum-bioprimed rice was reported to enhance rice growth in droughtstressed soils by triggering various respond mechanisms via many pathways. 45 Moreover, many Trichoderma species were reported as a potent producers of IAA and enzymes which enhanced plant tolerance to biotic and abiotic stress. Trichoderma longibrachiatum T6 (TL-6) significantly improved the growth of wheat and enhanced wheat tolerance to NaCl stress by reducing the transcriptional level of ethylene synthesis genes expression, and increasing IAA production gene expression.…”
Section: Discussionmentioning
confidence: 99%